Oil exploitation and human rights violations in Nigeria’s oil producing communities - Oluduro, Olubayo (Afrika Focus, 2012)
This work found that the continuous violations of human rights of the people to- gether with the poor regulation of oil MNCs in Nigeria are caused by a combination of several factors including: an inadequate legal framework which denies local inhabitants of their rights to land and natural resources; scant regard for environmental considerations; poor enforcement of the relevant environmental laws meant to protect the people and the environment; the Nigerian state ́s over-reliance on oil; prolonged military rule; a high level of corruption in the oil industry and the entire body polity of Nigeria; non-justiciability of the right to a clean environment; and weak institutions such as the judiciary and the National Human Rights Commission. All of these deficiencies continue to date. Coming at a time when governments worldwide are striving to ensure corporate accountability for their activities in host nations, this work is unique in that it incisively analyses how the national and regional institutions could be strengthened to provide effective protection against human rights abuses and ensure corporate accountability. The strengthening of these institutions and the promotion of a rights-based approach to environmental justice in the Niger Delta region therefore deserves concentrated attention and efforts by all actors in the industry.